Effect of virtual reality headset wear on the tear film: A randomised crossover study. - Turnbull, Philip R.K.; Wong, Joyce; Feng, Jasmine; Wang, Michael T.M.; Craig, Jennifer P. (Contact Lens & Anterior Eye, 2019)
Purpose: To compare the effects of virtual reality headset wear and conventional desktop computer display use on ocular surface and tear film parameters.Methods: Twenty computer operators were enrolled in a prospective, investigator-masked, randomised crossover study. On separate days, participants were randomised to 40 min of continuous virtual reality headset wear or conventional desktop computer display use. Outer eyelid and corneal temperatures, tear film lipid layer grade, and non-invasive tear film breakup time were measured at baseline and immediately following the 40-minute exposure period.Results: Virtual reality headset wear resulted in increases in outer eyelid (mean difference +0.5 ± 0.6 °C; p < 0.001) and corneal temperatures (mean difference, +0.4 ± 0.6 °C; p = 0.004), relative to conventional desktop computer display use. These increases were associated with significant improvements in tear film lipid layer grade (median difference, +1 grade; interquartile range, 0 to +2 grades; p < 0.001) and non-invasive tear film breakup time (mean difference, +7.2 ± 12.4 s; p = 0.02).Conclusions: Clinically significant improvements in lipid layer thickness and tear film stability were observed with virtual reality headset wear, despite producing only modest increases in ocular temperatures relative to conventional desktop computer display use. These findings would suggest that virtual reality headset wear demonstrates potential for dry eye relief for computer operators in the modern workplace environment.